Design of a High-Efficiency External Rotor Interior Permanent Magnet Synchronous Motor Without Magnetic Leakage Flux Path - Kyoung-Soo Cha; Jae-Hyun Kim; Soo-Gyung Lee; Min-Ro Park (Mathematics)
This paper proposes a high-efficiency design for an external rotor interior permanent magnet synchronous motor (IPMSM) that eliminates the magnetic leakage flux path. The conventional model based on an external rotor surface-mounted permanent magnet synchronous motor (SPMSM) is analyzed using a statistical method. Design directions are derived by comparing efficiencies at two major operating points with different motor characteristics. A V-shaped IPMSM is then proposed to increase the permanent magnet volume and reduce magnetic leakage. Design optimization is conducted using Gaussian process models (GPMs) constructed with a Latin hypercube design (LHD), and the optimal design is determined using a gradient descent algorithm. A prototype is fabricated to confirm manufacturability, and the improved efficiency of the proposed design is experimentally verified. The results demonstrate that the proposed IPMSM significantly outperforms the conventional SPMSM in terms of efficiency across both operating points.